Sensory analysis and chemical composition of ‘bourbon’ coffees cultivated in different environments - Figueiredo, Luisa Pereira; Borém, Flávio Meira; Ribeiro, Fabiana Carmanini; Giomo, Gerson Silva; Malta, Marcelo Ribeiro; Taveira, José Henrique da Silva (Coffee Science - ISSN 1984-3909, 2018)
Given the growing participation and appreciation of specialty coffees in the international market, coupled to the intrinsic quality of cultivar Bourbon for the production of differentiated coffees and the environmental diversity of Brazil, this study was conducted, with the objective to evaluate how the interaction between ‘Bourbon’ genotypes and different environments affect the sensory quality of coffees, besides relating the chemical composition (trigoneline, 5-CQA and caffeine) of beans with their sensory profile. Four Arabica coffee genotypes were evaluated: one of them is widely grown in Brazil (Mundo Novo) and three belong to the group of cultivar Bourbon. The genotypes were evaluated in a field experiment, in Lavras, MG; Santo Antônio do Amparo, MG and São Sebastião da Grama, SP. Thelatter was the most promising environment for the production of specialty coffees. Genotypes Yellow Bourbon IAC J9 and Yellow Bourbon/SSP were the most suitable for the production of specialty coffees. Regardless of culture environment, the genotype Yellow Bourbon/CM is not suitable for the production of specialty coffees. Caffeine content enabled coffee differentiation regarding beverage quality. Coffees with superior quality have lower caffeine contents. The content of 5-CQAallowed to differentiate environments.